Quality of life of children and adolescents with chronic kidney disease: a cross-sectional study. Issue 2 (22nd February 2019) - Francis, Anna; Didsbury, Madeleine S; van Zwieten, Anita; Chen, Kerry; James, Laura J; Kim, Siah; Howard, Kirsten; Williams, Gabrielle; Bahat Treidel, Omri; McTaggart, Steven; Walker, Amanda; Mackie, Fiona; et al.
Abstract : Objective: The aim was to compare quality of life (QoL) among children and adolescents with different stages of chronic kidney disease (CKD) and determine factors associated with changes in QoL. Design: Cross-sectional. Setting: The Kids with CKD study involved five of eight paediatric nephrology units in Australia and New Zealand. Patients: There were 375 children and adolescents (aged 6–18 years) with CKD, on dialysis or transplanted, recruited between 2013 and 2016. Main outcome measures: Overall and domain-specific QoL were measured using the Health Utilities Index 3 score, with a scale from −0.36 (worse than dead) to 1 (perfect health). QoL scores were compared between CKD stages using the Mann-Whitney U test. Factors associated with changes in QoL were assessed using multivariable linear and ordinal logistic regression. Results: QoL for those with CKD stages 1–2 (n=106, median 0.88, IQR 0.63–0.96) was higher than those on dialysis (n=43, median 0.67, IQR 0.39–0.91, p<0.001), and similar to those with kidney transplants (n=135, median 0.83, IQR 0.59–0.97, p=0.4) or CKD stages 3–5 (n=91, 0.85, IQR 0.60–0.98). Reductions were most frequent in the domains of cognition (50%), pain (42%) and emotion (40%). The risk factors associated with decrements in overall QoL were being on dialysis (decrement of 0.13, 95% CI 0.02 to 0.25, p=0.02), lower family income (decrement of 0.10, 95% CI 0.03 to 0.15, p=0.002) and short stature (decrement of 0.09, 95% CI 0.01 to 0.16, p=0.02). Conclusions: The overall QoL and domains such as pain and emotion are substantially worse in children on dialysis compared with earlier stage CKD and those with kidney transplants.